The effect of age on semen freezability of Swamp Buffalo bull in a commercial artificial insemination center - Nurul Isnaini; Tri Harsi; Wahyu Riza Zamani (Faculty of Animal Science, Universitas Brawijaya, 2019)
This study aimed to assess the effect of age on semen freezability (sperms motility before freezing, post-thawing, recovery rate, and straws production per ejaculate) of swamp buffalo bull kept in Lembang Artificial Insemination Center. A total of 115 ejaculates collected from one swamp buffalo bull at 5, 6 and 7 years old were included in the study. The results showed that the overall mean values of sperms motility before freezing, post-thawing, recovery rate, and straws production per ejaculate of swamp buffalo bull were 62.13%, 43.61%, 62.16%, and 114.16 doses, respectively. The age of bull did not show significant (P>0.05) effect on sperms motility before freezing, however the sperms motility post-thawing, recovery rate, and straws production per ejaculate was influenced (P<0.01) by bull age. At seven years old, the poorest (P<0.01) post-thawing sperms motility and recovery rate were noted in comparison to 5 and 6 years old, nevertheless the difference in post-thawing sperms motility was only less than 3% point, which was not biologically important. On the other hand, the semen collection at seven years old had a higher (P<0.01) straws production per ejaculate than those at 5 and 6 years old (133.70 vs. 106.39 and 90.61 doses, respectively). In conclusion, this study provides evidence that the semen freezability of swamp buffalo bull is varied among the age with the peak frozen semen production was achieved at seven years old.